Implikasi yuridis parate eksekusi obyek hak tanggungan - Lydia Kurnia Putri Rosari; Imam Nur Koeswahyono; Diah Aju Wisnuwardhani (Jurnal Cakrawala Hukum, 2022)
To analyze and study the juridical implications of separate execution on the object/s of mortgage are the objectives to be achieved in this research and also to find out what are the obstacles faced by the Bank PT. Central Bank Asia Tbk. Kediri Branch in implementing para te execution with the object of the mortgage. The method used in this research is empirical legal research with interview data collection techniques, literature studies, and documentation. The results of the research with the method above show the obstacles that might occur is an obstacle that came from the debtor's side, for example, the existence of resistance from the debtor or third party and the emptying of the object of the liability right. The obstacle from the creditor's side is the difficulty in finding auction buyers for the object of the execution auction. The juridical implication of the execution parade with the object of collateral is to obtain creditor assurance regarding the repayment of his debt from the debtor, in addition to accelerating the repayment process of creditors when the debtor defaults by giving the creditor the right to sell the Collateral Right Object of his own power through a public auction.How to cite item: Rosari. L.K.P., Koeswahyono I., Wisnuwardhani. D.A. (2022). Implikasi Yuridis Parate Eksekusi Objek Hak Tanggungan. Jurnal Cakrawala Hukum, 13(1). doi:10.26905/idjch.v13i1.5189.